Breeding Performance of Catla, Catla catla (Ham.) Fed with Different Formulated Diets - J.K., Manissery; K., Venkateshmurthy; B., Gangadhara; M.C., Nandeesha (Fishery Technology, 2025)
Breeding performance of catla, (Catla catla) was assessed through feeding trial for three months. Test diets with 30% protein (diet B) and 35% protein (diet C) were developed using a combination of rice bran, groundnut cake and fish meal. The proportion of these ingredients was reduced in diet D and replaced with horse gram, black gram, broken cake, rice and maize. Control diet (diet A) having 25% protein was formulated with 1:1 mixture of rice bran and groundnut oil. The breeding weight loss in females was lower (P<0.05) in treatments A (7.43%) and D (6.37%) and higher in treatments B (8.36%) and C (9.00%) and the difference was significant (P< 0.05). Fecundity, fertilization, hatching and length and weight of hatchlings were the lowest (P<0.05) in fish fed diet A and did not vary (P>0.05) between treatments B and C. Diet D performed superior to diet A in terms of fecundity, percentage of fertilization and hatching and length and weight of hatchlings. Among the different treatments, the highest weight of hatchlings was recorded in treatment D.